526 InhibigenTM-specific responses suppress anti-tumor immunity and promote tumor growth. (9th November 2020) - DeVault, Victoria; Dadali, Tulin; Starobinets, Hanna; Lema, Kevin; Rinaldi, Stephanie; Odeh, Osaruese; Arnold, Julie; Sheehan, Dylan; Nguyen, Cindy; Dowal, Louisa; Flechtner, Jessica; Visintin, Alberto; et al.
Abstract : Background: Personalized cancer immunotherapies can generate potent antitumor responses yet finding the right targets remains challenging. The ATLAS TM platform employs ex vivo functional screening of tumor mutations using autologous cells to identify patient-specific neoantigens. Stimulatory neoantigens are identified by upregulation of inflammatory cytokine secretion and can be employed in vaccines or cell therapies. Conversely, ATLAS also identifies inhibitory neoantigens (termed Inhibigens) that lead to cytokine downregulation, and in murine models accelerate tumor growth and abrogate the efficacy of otherwise-protective vaccines. Here we further explore Inhibigen mechanism of action in humans and mice including whether checkpoint inhibition (CPI) can ameliorate Inhibigen-accelerated tumor growth. Methods: Human and mouse ATLAS screens were performed as previously described. 1 ATLAS-identified stimulatory or Inhibigen peptide vaccines were evaluated in a therapeutic B16F10 melanoma tumor model ± CPI. Immune responses were measured using ELISPOT, flow cytometry, and immunohistochemistry (IHC). Results: In the GEN-009 personalized neoantigen vaccine trial (NCT03633110 ), Inhibigens were observed in 92% of patients (N=39). Of total mutations screened, 16% (1.8 - 47.5%) were classified as Inhibigens, which were found more often in the CD4 + (mean 10.3%; 0.5 - 42%) versus CD8 + T cell subset (mean 6.1%; 1.2–23%). No relationship between Inhibigen-specific responses and tumor type or mutational burden were observed. To study the functional effects of Inhibigen vaccination in vivo, a B16F10 mouse melanoma model was employed. Inclusion of Inhibigens in an otherwise protective vaccine abrogated efficacy and correlated with decreased T cell responses to vaccine antigens as well as a global depression of T cell cytokine secretion. Early experiments suggest that these decreases are not due to MHC competition. In addition, administration of a therapeutic vaccine containing an Inhibigen led to reduced tumor infiltration of CD8 + T cells and myeloid populations. A corresponding increase of classical Tregs in the tumor or periphery was not observed. Surprisingly, preliminary data show combination therapy with anti-CTLA4 partially ameliorated Inhibigen-accelerated tumor growth but anti-PD1 provided no additional benefit. Conclusions: The nearly ubiquitous presence of Inhibigens in human cancer patients and the demonstrated pro-tumor effects in mice suggest that ATLAS-identified Inhibigens must be considered and omitted in the design of cancer immunotherapies. Furthermore, in mice, CPI co-administration has a modest (anti-CTLA4) or no (anti-PD1) effect on Inhibigen-accelerated tumor growth suggesting that Inhibigen profiling could guide CPI selection or predict clinical outcome. These data confirm the benefits of the ATLAS platform for neoantigen and Inhibigen identification. Ethics Approval: All animal studies were undertaken in conformity with the Cambridge, MA City Ordinance 1086 of the city's Municipal Code and in accordance with the policies and protocols approved by Genocea's Institutional Animal Care and Use Committee (IACUC). Reference: Nogueira C, Kaufmann JK, Lam H, Flechtner JB. Improving cancer immunotherapies through empirical neoantigen selection. Trends in Cancer 2018 Feb;4(2):97–100